2020
DOI: 10.1021/acssensors.9b02486
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Colorimetric Detection of Pyrophosphate Ions by Inhibitive Nanozymatic Carbon Dots

Abstract: The pyrophosphate ion (P 2 O 7 4− , PPi) plays a critical role in various biological processes and acts as an essential indicator for physiological mechanism investigations and disease control monitoring. However, most of the currently available approaches for PPi species detection for practical usage still lack appropriate indicator generation, straightforward detection requirements, and operation convenience. In this study, a highly sensitive and selective PPi detection approach via the use of nanozymatic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 73 publications
(146 reference statements)
1
46
0
Order By: Relevance
“…For these devices, the use of composite materials is common, and is often performed in conjunction with supporting polymer backings to increase device robustness. On the other hand, the porosity of the paper substrate allows the material hydrophilicity to be modified through impregnation of hydrophobic substances, such as photoresist [24], wax [26][27][28], and polydimethylsiloxane [29]. These hydrophobic chemicals can penetrate into the paper substrate pores, rendering the affected areas hydrophobic.…”
Section: Materials Selection and Device Designmentioning
confidence: 99%
See 2 more Smart Citations
“…For these devices, the use of composite materials is common, and is often performed in conjunction with supporting polymer backings to increase device robustness. On the other hand, the porosity of the paper substrate allows the material hydrophilicity to be modified through impregnation of hydrophobic substances, such as photoresist [24], wax [26][27][28], and polydimethylsiloxane [29]. These hydrophobic chemicals can penetrate into the paper substrate pores, rendering the affected areas hydrophobic.…”
Section: Materials Selection and Device Designmentioning
confidence: 99%
“…(B) An improved bulk material-electrode interface design for a sponge-based piezoresistive sensor. Adapted with permission from[27,37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Fluorescence sensing and bioimaging techniques have become important approaches in biomedical applications because they can provide real-time information about the location and amount of the biomarkers. In recent years, various fluorescent probes have been prepared for PPi detection including organic probes, 14,15 quantum dots, 16,17 silver nanoclusters, 18 etc. Guo et al reported an organic fluorescent probe for in vivo Cu 2+ /PPi detection based on 7-substituted coumarin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, monitoring enzyme activities by using LFA test strips remains inaccessible with the current molecular binding approach, as the detection of enzyme activities would require the enzyme to have a chemical reaction with its corresponding substrate. Although many paper-based chromogenic dye methods have been reported for rapid analysis of small reactive molecules and enzymes, the chromogenic dyes must undergo clearly distinguishable color changes that can be displayed in an obvious and easy-to-interpret manner. Typically, a change of color requires a significant shift in the concentration of the chromogenic dye to its product. In low analyte concentrations, many chromogenic dyes, e.g., Bodipy, carbon dots, and rhodamine, shows only subtle color changes, which may not be discernible to a nonexperienced user. Comparatively, a test line observed against the white background membrane of the LFA test strip can give a clear and distinct band.…”
mentioning
confidence: 99%